Nephrotic Syndrome in a Patient with Relapsed of Chronic Myeloid Leukemia after Peripheral Blood Stem Cell Transplantation - Bee, P.C.; Gan, G.G.; Sangkar, V.J.; Haris, A.R. (Malaysian Medical Association, 2008)
Nephrotic syndrome (NS) is a well documented complication after allogeneic peripheral blood stem cell transplantation. It is usually due to autoimmune glomerulonephritis and thought to be a clinical manifestation of graft versus host disease. NS has also been reported to be associated with other hematological malignancies. We report a case of nephrotic syndrome in a patient who relapsed after allogeneic peripheral blood stem cell transplantation (PBSCT) for chronic myeloid leukemia (CML). The renal biopsy was suggestive of minimal change disease. There was no other evidence of graft versus host disease. He was treated with high dose prednisolone, with no response and finally succumbed to the underlying disease.